2017
DOI: 10.4314/ajcem.v18i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of extended-spectrum beta-lactamase producing <i>Enterobacteriaceae</i> causing urinary tract infections in Ouagadougou, Burkina Faso

Abstract: 140Conclusion:35% des souches cliniques étaient productrices de BLSE. Une fréquenceélevée des entérobactéries productrices de BLSE aétéobservée chez l'espèceE. coli et Klebsiellaspp parmi les souches cliniques testées. Les résultats montrent une nécessité de mettre en place un système de surveillance des souches productrices de BLSE au Burkina Faso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The genera isolated from our greywater samples are often recognized as opportunistic pathogens associated with urinary tract, bloodstream and respiratory infections. In this context, infections caused by ESBL-producing bacteria represent an emerging health problem in Burkina Faso, as already reported by some authors ( Kpoda et al 2017). Indeed, the presence of these MDR species in untreated greywater discharged into the environment could accelerate the transfer of ESBL genes to pathogenic bacteria, posing a clear threat to public health.…”
Section: Biochemical Characteristics Of Mdr Bacterial Strainsmentioning
confidence: 63%
See 1 more Smart Citation
“…The genera isolated from our greywater samples are often recognized as opportunistic pathogens associated with urinary tract, bloodstream and respiratory infections. In this context, infections caused by ESBL-producing bacteria represent an emerging health problem in Burkina Faso, as already reported by some authors ( Kpoda et al 2017). Indeed, the presence of these MDR species in untreated greywater discharged into the environment could accelerate the transfer of ESBL genes to pathogenic bacteria, posing a clear threat to public health.…”
Section: Biochemical Characteristics Of Mdr Bacterial Strainsmentioning
confidence: 63%
“…are often considered opportunistic pathogens associated with urinary tract, bloodstream, respiratory tract, and skin infections (Tong et al 2015;Noman et al 2022). In this context, infections with ESBL-producing bacteria are also an emerging health problem in West African populations (Kpoda et al 2017). As mentioned earlier, these households are often not connected to sewerage systems, leading to higher levels of exposure to wastewater.…”
Section: Biochemical Characteristics Of Mdr Bacterial Strainsmentioning
confidence: 99%
“…They found that E. coli was the predominant cause of urinary tract infection 39. According to the study conducted by Kpoda et al 16 on the susceptibility of extended spectrum betalactamase producing Enterobacteriaceae causing urinary tract infections in Ouagadougou, Burkina Faso, a total of 324 isolates of Enterobacteriaceae were identified during the study period, including 211 (65 %) E. coli, 75 (23 %) Klebsiella spp., 18 (6 %) Enterobacter spp., 11 (3 %) Proteus spp., 5 (2 %) Citrobacter spp., and 3 (1 %) for Serratia spp.…”
Section: Discussionmentioning
confidence: 99%